6‐Deoxyhexoses from l‐Rhamnose in the Search for Inducers of the Rhamnose Operon: Synergy of Chemistry and Biotechnology. Issue 35 (21st July 2016) - Liu, Zilei; Yoshihara, Akihide; Kelly, Ciarán; Heap, John T.; Marqvorsen, Mikkel H. S.; Jenkinson, Sarah F.; Wormald, Mark R.; Otero, José M.; Estévez, Amalia; Kato, Atsushi; Fleet, George W. J.; Estévez, Ramón J.; et al.
Abstract: In the search for alternative non‐metabolizable inducers in thel ‐rhamnose promoter system, the synthesis of fifteen 6‐deoxyhexoses froml ‐rhamnose demonstrates the value of synergy between biotechnology and chemistry. The readily available 2, 3‐acetonide of rhamnonolactone allows inversion of configuration at C4 and/or C5 of rhamnose to give 6‐deoxy‐d ‐allose, 6‐deoxy‐d ‐gulose and 6‐deoxy‐l ‐talose. Highly crystalline 3, 5‐benzylidene rhamnonolactone gives easy access tol ‐quinovose (6‐deoxy‐l ‐glucose), l ‐olivose and rhamnose analogue with C2 azido, amino and acetamido substituents. Electrophilic fluorination of rhamnal gives a mixture of 2‐deoxy‐2‐fluoro‐l ‐rhamnose and 2‐deoxy‐2‐fluoro‐l ‐quinovose. Biotechnology provides access to 6‐deoxy‐l ‐altrose and 1‐deoxy‐l ‐fructose. Abstract : Rhamnonolactone chiron perfection : The efficient production of fifteen 6‐deoxy‐sugars froml ‐rhamnose by a synergy of chemical synthesis and biotechnology to find alternative non‐metabolizable inducers to rhamnose for thel ‐rhamnose operon is described. Several inducers with different levels of activity were identified.